43/9=n+7/9

Simple and best practice solution for 43/9=n+7/9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 43/9=n+7/9 equation:


n in (-oo:+oo)

43/9 = n+7/9 // - n+7/9

43/9-n-(7/9) = 0

43/9-n-7/9 = 0

4-n = 0 // - 4

-n = -4 // * -1

n = 4

n = 4

See similar equations:

| 1/18=b-5/6 | | 2/5t=-1/5 | | 2/5x=4 | | -20/3=b-7 | | -1/7k=-6/49 | | 0=w-2/9 | | 5k=-10 | | d+1=17/10 | | -23/55=w-3/5 | | 1/2+d=21/2 | | n+3=23/9 | | 17/10=x+2 | | b+2=25/9 | | 75/7=a+10 | | -1/2m=3/2 | | -5/9+m=103/9 | | 35/4=n+9 | | -7=d-2 | | d-1=-3/5 | | -1/3m=5/3 | | 2n=3/2 | | -7/15=k+1/3 | | k+3/10=73/10 | | n+2/7=-13/28 | | 3/7k=33/7 | | t/3=-3/7 | | 1+k=4 | | w+7=15/2 | | 51/56=b+5/8 | | 3/7w=24/7 | | 2/3a=2/3 | | 3+b=19/7 |

Equations solver categories